Experimental Research and Modeling of Particle Deposition in Ventilation Ducts. (21st October 2013) - Fan, Hongming; Hua, Jing
Abstract : The model to predict particle deposition velocity on rough walls in fully developed turbulent duct flows has been developed in previous studies. For particle deposition model boundary conditions, it is assumed that the concentration of the particle is zero on the surface and the resuspension velocity is constant. However, the resuspension velocity may not be constant with the increase in mass of the deposited dust. To analyze the behavior of resuspension in air flow, a set of experiments were designed and conducted. Results showed that there was a linear relationship between the mass of resuspension and deposited dust. Also, the particle deposition model was improved by adding a resuspension item to the equation, and the steady-state equation was developed into a time-varying equation. The analysis results are presented in this paper.